2010
DOI: 10.1038/jhg.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in the RAGE gene with serum CRP levels and coronary artery disease in the Chinese Han population

Abstract: The role of an advanced glycation end product/receptor for advanced glycation end product (AGE/RAGE) system in the pathogenesis of coronary artery disease (CAD) is not fully understood. To clarify whether polymorphisms of the RAGE gene were related to CAD, we performed a case-control study in Chinese Han patients. The allele frequencies and genotype distribution combinations of the À429T/C, 1704G/T and G82S polymorphisms of the RAGE gene were compared in 200 cases of hypertension (HT), 155 cases of CAD combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
1
26
1
Order By: Relevance
“…Hou et al reported that hypertensive patients had higher serum hs-CRP levels than controls with normal blood levels [55]. The serum CRP was significantly associated with the G82S variant in the Chinese Han population with CAD [41]. Serum CRP concentration has been reported to be in relation to ischemic stroke subtype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hou et al reported that hypertensive patients had higher serum hs-CRP levels than controls with normal blood levels [55]. The serum CRP was significantly associated with the G82S variant in the Chinese Han population with CAD [41]. Serum CRP concentration has been reported to be in relation to ischemic stroke subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Jang et al have reported that subjects with the SS homozygous mutation of the G82S polymorphism had increased risk factors for cardiovascular disease compared with those bearing at least one G allele in non-diabetic and non-obese Koreans [39]. G82S polymorphism in the RAGE gene is associated with diabetic retinopathy in Chinese population [40], but no positive association between the polymorphisms at 82G/S and the presence and severity of CAD [41]. The association of the G82S polymorphism of RAGE with diabetic retinopathy was confirmed in the population of southern India [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 82G>S variant also was significantly influence the serum inflammatory marker, such as C reaction protein level in the Chinese Han population with coronary heart disease [30]. Factors contributing to chronic inflammation appear to be associated with increased risk of ovarian cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…AGER, a cell surface protein, is a multi-ligand receptor of the immunoglobulin superfamily that is expressed in combination with certain active ligands including advanced glycosylation end-products (AGEs), amyloid-b protein, and several members of the S100 family (Gao et al, 2010). The formation of the AGER complex primarily includes components such as non-enzymatic glycation proteins and lipoproteins, and its protein structure is comprised of an extracellular domain and a single-transmembrane domain with a short cytosolic tail (Fang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%